Contribution of respiratory heat loss to heat balance in Thoroughbred horses performing near maximal exercise under thermoneutral and hot-humid conditions - Meintjes, R. (University of Pretoria, 2013)
Thesis (DPhil)--University of Pretoria, 2000.